Bridging the Gap Between Neurocognitive Processing Theory and Performance Validity Assessment among the Cognitively Impaired: A Review and Methodological Approach. (10th November 2014) - Leighton, Angela; Weinborn, Michael; Maybery, Murray
Abstract Bigler (2012) and Larrabee (2012) recently addressed the state of the science surrounding performance validity tests (PVTs) in a dialogue highlighting evidence for the valid and increased use of PVTs, but also for unresolved problems. Specifically, Bigler criticized the lack of guidance from neurocognitive processing theory in the PVT literature. For example, individual PVTs have applied the simultaneous forced-choice methodology using a variety of test characteristics (e.g., word vs. picture stimuli) with known neurocognitive processing implications (e.g., the "picture superiority effect"). However, the influence of such variations on classification accuracy has been inadequately evaluated, particularly among cognitively impaired individuals. The current review places the PVT literature in the context of neurocognitive processing theory, and identifies potential methodological factors to account for the significant variability we identified in classification accuracy across current PVTs. We subsequently evaluated the utility of a well-known cognitive manipulation to provide a Clinical Analogue Methodology (CAM), that is, to alter the PVT performance of healthy individuals to be similar to that of a cognitively impaired group. Initial support was found, suggesting the CAM may be useful alongside other approaches (analogue malingering methodology) for the systematic evaluation of PVTs, particularly the influence of specific neurocognitive processing components on performance. (JINS, 2014, 20, 873–886)